Fabrication of MnO2/g-C3N4 hetero-junction for hydrogen production and rhodamine B/methylene blue dye degradation - Ahmad, Khursheed; Chaudhary, Archana; Raza, Waseem; Alsulmi, Ali; Kim, Haekyoung (Optical Materials, 2023)
Over the past few decades, significant progress has been made in the area of clean and renewable energy resources to cope with the rapid diminish of fossil fuels. To suffice this purpose, photocataytic hydrogen production using heterojunctions is drawing a lot of attention. For this purpose a MnO2/g-C3N4 heterojunctions has been fabricated using hydrothermal method. The fabricated sample has been characterized by PXRD, SEM and EDX analysis. The XPS analysis reveals about the presence of Mn, C, N and O elements in the sample. The bandgap for MnO2/g-C3N4 narrowed to 1.75 eV, favouring the harvesting of visible-light. In the photocatalytic H2 evolution reaction (HER), MnO2/g-C3N4 heterojuctions exhibited promising results with 3855 μmol g−1 H2 production via Z-scheme mechanism, where e− produced in MnO2 are accumulated in the valance band of g-C3N4, increasing the lifetime of generated e− and h+. Fabricated MnO2/g-C3N4 heterojunctions have also been used for degradation of industrial dye viz. Rhodamine B (RhB) and Methyl orange (MO).
CRIS-Team Scopus Importer:2024-12-16
Keywords: Hydrogen evolution reaction (HER); Methyl orange; MnO; Rhodamine B; Z-scheme mechanism